Effects of human probiotics on memory and psychological and physical measures in community-dwelling older adults with normal and mildly impaired cognition: results of a bi-center, double-blind, randomized, and placebo-controlled clinical trial (CleverAge biota) - Bartos, Ales; Weinerova, Josefina; Diondet, Sofia (Frontiers in Aging Neuroscience, 2023)
Objectives: This study presents results of our randomized clinical trial studying the effect of human probiotics on memory, psychological and physical measures following our study protocol registered at clinicaltrials.gov NCT05051501 and described in detail in our previous paper (Bartos et al., 2022). Methods: Community dwelling participants aged between 55 and 80 years were randomly assigned to receive a single dose of 106 colony forming units of human Streptococcus thermophilus GH, Streptococcus salivarius GH NEXARS, Lactobacilus plantarum GH and Pediococcus pentosaceus GH or placebo. A cross-over design allowed each group to receive probiotics and placebo for 3 months each in reverse order. A small subset of participants was examined online due to Covid-19 pandemic. After 6 months a small number of volunteers was additionally assessed after the next 2 months without any intervention. Primary outcome measures included changes in cognitive functions assessed using brief tests and a neuropsychological battery and changes in mood assessed using validated questionnaires. Secondary outcome measures included changes in self-report and subjective measures using depression and anxiety questionnaires, seven visual analogue scales of subjective feelings (memory, digestion, etc.), and physical performance. Results: At baseline, the probiotic-placebo group A (n=40, age 69±7 years, education 16±3 years, 63 % females, body mass index 295±6, subjective memory complaint in 43 %) did not differ from the placebo-probiotic group B (n=32) in any of the sociodemographic characteristics and evaluated measures including cognitive status. At follow-up visits after 3, 6, and 8 months, no cross-sectional differences in any of the measures were found between the groups except worse sentence recall of the ALBA test after 3 months of probiotic use. There were no longitudinal score differences in any of the cognitive tests but one in either group after the first 3 months and between examinations at 3 and 6 months. The only change was observed for the TMT B test after the first three months but not after the second three months. Conclusions: The treatment with human probiotics and prebiotics did not improve cognitive, affective, or physical measures in the community-dwelling individuals with normal or mildly impaired cognitive functions.